BS EN 17415-3. District cooling pipes. Bonded single pipe systems for directly buried cold water networks. Part 3. Factory made steel valve assembly for steel or plastic service pipe, polyurethane thermal insulation and a casing of polyethylene (16th July 2020) - British Standards Institution,
No abstract available